Agroclimatic zone-wise prevalence of biofilm forming methicillin resistant staphylococcus aureus in West Bengal - BARDHAN, RAJARSHI; PAUL, ADITYA; SAMANTA, INDRANIL; BATABYAL, KUNAL; DEY, SAMIR; SARKAR, UTTAM; JOARDAR, SIDDHARTHA NARAYAN (The Indian Journal of Animal Sciences, 2024)
The present study envisages the prevalence of biofilm producing, methicillin resistant Staphylococcus aureus, isolated from cattle milk of different agro-climatic zones of an eastern state of India, West Bengal. The milk samples (n=168) were collected from three predominant agro- climatic zones of South Bengal, viz. new alluvial, coastal saline and red laterite. A total of 146 Staphylococcus aureus isolates were recovered, confirmed by biochemical tests and polymerase chain reaction (PCR). Through PCR of mecA gene, it was found that 45 strains were methicillin resistant, encompassing 28.57% new alluvial zone, 30.19% red laterite region and 29.16% coastal saline region. Determination of biofilm formation was done, both phenotypically by microtiter plate method and genotypically by PCR of icaA and icaD genes, specific for biofilm formation in Staphylococcus aureus. Phenotypic study revealed that 14 isolates were strong biofilm producers, 79 were moderate and the 47 were weak biofilm producers. PCR studies also showed that a total of 30 isolates were icaA positive and 25 isolates were icaD positive. Although no significant difference was found in the occurrence of icaA positive isolates, the possession of icaD by the Staphylococcus aureus isolates varied significantly according to different agro-climatic zones.